The complete air fryer cookbook for beginners : 625 recipes : fry, bake, grill, & roast most wanted meals - Eva Garcia-Diaz (Edinburgh, UK : America's Food Hub, 2020)
"Do you want to kickstart 2020 cooking with your Air Fryer but don't know where to start? Quit worrying! In this cookbook, you'll learn how to not only start, but love, your Air Fryer, which will guide you to amazing meals in the most affordable, quick & easy way possible. Along the way, you'll learn to cook 625 of the highest quality super tasty Air Fryer recipes, offering tons of scientifically proven health benefits, such as improving your appetite, cholesterol, blood pressure and reversing diabetes. Rest assured, you, the Air Fryer beginner, will learn how to master your Air Fryer in no time!"--Amazon
Keywords: Cookbooks; Hot air frying; Quick and easy cooking